EVALUATING THE SYNERGISTIC EFFECT AND SAFETY PROFILE OF FENTANYL 0.5% VERSUS CLONIDINE IN COMBINATION WITH 0.5% BUPIVACAINE FOR SUBARACHNOID BLOCK IN ELECTIVE LOWER LIMB SURGERIES - Shilpa.P.H; Shruthi R Nayak; Karthik Kumar; Raghavendra Biligiri Sridhara; Krishna Prasanth Baalann (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Subarachnoid block (SAB) stands as a cornerstone in regional anesthesia for various surgical procedures, offering effective analgesia and muscle relaxation while minimizing systemic side effects. In elective lower limb surgeries, the choice of adjuvants to enhance the efficacy and safety of local anesthetics remains a subject of ongoing research and clinical interest [1].Among the adjuncts explored for SAB, fentanyl and clonidine have gained significant attention due to their potential to augment analgesia and prolong the duration of sensory and motor blockade [2, 3]. Fentanyl, a potent opioid analgesic, and clonidine, an alpha-2 adrenergic agonist, have distinct mechanisms of action that complement the effects of local anesthetics [2]. Fentanyl acts primarily on mu-opioid receptors in the spinal cord, modulating pain perception, while clonidine exerts its effects through the modulation of norepinephrine release, leading to analgesia and sympatholytic properties [3]. These adjuncts have been widely studied individually in SAB, demonstrating promising results in terms of prolonging the duration of anesthesia and reducing the need for supplemental analgesia [4, 5]. However, the comparative efficacy and safety of fentanyl and clonidine when combined with 0.5% bupivacaine in SAB for elective lower limb surgeries remain to be fully elucidated [1, 6]. While both adjuncts have demonstrated beneficial effects, their potential synergistic interactions and respective safety profiles warrant further investigation [1, 6]. Understanding the relative merits and drawbacks of these adjuncts is crucial for optimizing perioperative pain management strategies and enhancing patient outcomes. Therefore, this study aims to assess the synergistic effect and safety of adding fentanyl 0.5% compared with clonidine to 0.5% bupivacaine in SAB for elective lower limb surgeries.